AN ALTERNATIVE STUDY OF ADAPTIVE PARTITION DESIGN FROM COW DUNG - Ing Julita; Rully Damayanti; Timoticin Kwanda (DIMENSI (Journal of Architecture and Built Environment), 2022)
The use of cow dung as a local and organic building material in Indonesia has been carried out in various forms because it has similar characteristic of cement. The choice of using cow dungs is based on recent sustainable issues and the effects on the built environment such as farming sector and natural resources. One of the solutions to the sustainable issues that occur is the adaptive building concept, where this concept will focus on the user life cycle, building materials, and construction such as wall or partition panels. The cow dung material will act as an adaptive medium and it will be constructed as partition wall. This paper presents the design of an adaptable construction with modular partition wall from cow dung mix. The result is a sustainable cow dung partition wall that applied in an apartment layout unit which can adapt to different user life cycle and demands.